(untitled) (International journal of artificial intelligence, 2026)
This article presents the scientific and theoretical basis for the comprehensive evaluation of tomato (Solanum lycopersicum L.) genotypes under protected cultivation according to phenological and biometric traits, fruit-quality indicators, and biofortification potential. The research direction is focused on assessing gene-bank accessions and hybrids for Fe, Zn, Ca, Se, lycopene, beta-carotene, ascorbic acid, and antioxidant activity; identifying donor genotypes with high nutritional value; and developing a breeding-genetic model suitable for protected cultivation. The article substantiates the scientific importance of creating biofortified tomato varieties through the integrated use of phenological, morphological, biometric, biochemical, mineral, and statistical analyses.